Key Factors Needed for Developing a Higher Education Cross-Campus Learning Environment in a Nordic Context - Nykvist, Shaun Sydney; De Caro-Barek, Veruska; Støckert, Robin; Lysne, Dag Atle (Frontiers in Education, 2021)
The use of digital technologies and online tools to support both students and educators has become synonymous with transforming learning within Higher Education, particularly within post graduate courses. It can be argued that the recent push for transforming Higher Education aligns itself with the notion that postgraduate students need more flexible learning opportunities while still retaining access to high quality engaging and collaborative pedagogical approaches. This paper reports on an exploratory case study that focuses on cross campus/university collaboration and flexible learning opportunities for students studying a masters level degree in the area of Music, Communication and Technology (MCT) within a Nordic context. The research question guiding the study is “What factors do educators in a hybrid cross-campus learning environment identify as essential for providing a supportive learning experience for students?” A pedagogy, space and technology (PST) framework underpins the development of this program and forms the basis for its development. The findings from our research identify three themes that need to be considered when attempting to design and implement high quality learning opportunities for students studying a largely synchronous hybrid music, communications and technology program. These themes were flexibility, trust and the human element, and ownership. The findings also highlight the need for a renewed focus on pedagogical approaches that can be adapted and continually revised to meet the changing needs of students in a synchronous hybrid learning space.